An improved mesh refinement method to study the tip vortex cavitation of a marine propeller. (3rd October 2022) - Zhu, Wencai; Zhou, Feng; Zhao, Jinpeng
ABSTRACT: The main purpose of this research is to develop a mesh refinement method for tip vortex cavitation (TVC) simulation. The mesh size of the blade surface is determined by studying the influence of mesh on the open water characteristics. The mesh size of the tip vortex wake is determined by analyzing the influence of mesh on the structure of the tip vortex. In the process of increasing the mesh resolution, a hollow cylinder is used to refine the mesh of the tip vortex wake. Based on the structure of the tip vortex, the adaptive mesh refinement (AMR) technique is used to simulate the TVC behaviour. The Q -criterion and wall distance are used as field function variables to refine the mesh in the region where TVC is likely to occur. Numerical results show that the mesh refinement method proposed in this paper is very effective in simulating TVC.